Loss of 5-HT2C receptor function alters motor behavior in male and female mice with and without spinal cord injury - Sim, Margaret I.; Birch, Derin; Mahrous, Amr A.; Heckman, C.J.; Tysseling, Vicki M. (Frontiers in Neural Circuits, 2025)
The 5-HT2C receptor is involved in the regulation of spinal motor function, specifically in both volitional and involuntary motor behavior. It contributes to various aspects of voluntary movement, such as locomotion, gait, coordination, and muscle contractions. It also contributes to involuntary motor behavior (i.e., spasms), which affects many individuals with spinal cord injury. Despite its known involvement in motor function, additional research in uninjured mice is required to assess whether specific gait parameters and muscle contractility are directly linked to the 5-HT2C receptor. In injured mice, further research is needed to determine whether the expression of the 5-HT2C receptor is altered in the lumbar and sacral spinal cord after injury. It is also necessary to determine whether voluntary locomotion, involuntary motor behavior, or the expression of this receptor is influenced by sex, as it is unknown if there is a difference in 5-HT2C receptor expression between male and female mice. The aim of this study is to investigate volitional and involuntary motor behavior of male and female uninjured and spinal cord-injured knock-out mice. Mice that express a non-functional form of the 5-HT2C receptor were compared to typical-functioning wildtype mice. Volitional behavioral assessments revealed mild strength and stability deficits in the knock-out mice when compared to wildtype mice. We also compared the capacity of spinal cord tissue to generate sensory evoked activity, and it was revealed that male knock-out mice exhibited less involuntary motor behavior both ex vivo and in vivo than male wildtype mice. Western blot analysis revealed that injury status, sex, and genotype affected the relative expression of the 5-HT2C receptor in both the lumbar and sacral spinal cord, with female KO mice exhibiting a compensatory mechanism post-SCI via upregulation of the 5-HT2A receptor. Through a comprehensive approach combining behavioral assessments, electrophysiological experiments, and whole-tissue protein analysis, our findings provide strong evidence that the 5-HT2C receptor is differentially regulated by sex, genotype, and spinal cord injury. These findings underscore the importance of considering sex as a biological variable and suggest that future therapeutic strategies targeting the 5-HT2C receptor account for sex-specific differences in 5-HT2C receptor expression and function.